Location-Based Service with Interactive Mapping in Food Feed Mobile App (FeatiGo) - Abdul Rahman, Mat; San, Nah Sze; Wei King, Tiong (Akademia Baru Publishing (M) Sdn Bhd, 2026)
Food serves as a cornerstone of human life, connecting sustenance with exploring diverse culinary experiences. With the increasing number of individuals embarking on gastronomic adventures, the demand for accessible and customized food information becomes paramount. Existing mobile applications offer a range of functionalities, primarily focused on posting food information, searching for eateries, filtering options and providing eatery details, frequently facilitated by location-based services. However, there remains a gap in the market for a comprehensive platform that consolidates these features with an interactive map in one mobile app, requiring users to navigate between multiple applications. The study tackles the issue of sifting through vast online food data by developing the FeatiGo mobile app, which uses location-based services and interactive mapping to provide a unified platform for effortless dining discovery. User testing encompassed functionality and instrumental testing alongside usability evaluation, yielding positive results and feedback on usability with a mean satisfaction score of 90.72%. Our app has proven to provide tailored food information, enriching culinary experiences by leveraging location in the digital mobile era.